The Utilization Of Golden Snail Shell For Domestic Liquid Waste In The Banksa Suci Cihuni: Pemanfaatan Cangkang Keong Mas untuk Limbah Cair Domestik di Banksa Suci Ciheuni - Ismi Nurlatifah; Siti Maftukhah; Dine Agustine (Universitas Lancang Kuning, 2023)
Community service in the form of domestic liquid waste treatment at Banksa Suci (Cisadane River Garbage Bank) Ciheuni is motivated by domestic wastewater flowing into the Cisadane river and passing through the Banksa Suci Ciheuni park which has been polluted with black waste water showing. The waste water comes from the area around the Banksa Suci Ciheuni park which consists of residential areas, offices and hospitals. Polluted wastewater that flows into the Cisadane river can contaminate the Cisadane river body and its ecosystem. This activity aims to purify the waste sample water so that it is in accordance with the quality standards. This community service is carried out by adding golden snail shell powder to wastewater, with a concentration of 0%, 10% and 20% then stirring and filtering, then analyzed in the laboratory. The results of the analysis show that the golden snail shell is able to reduce the turbidity of the holy banksa wastewater.